Bridging Gender Gaps in Climate-Smart Agriculture in Africa: How to Overcome Them - Boudalia, Sofiane; Teweldebirhan, Mahilet Dawit; Huyer, Sophia (Accelerating Impacts of CGIAR Climate Research for Africa, 2025)
Closing the gender gap in African agriculture is key to boosting productivity, resilience, and food security while strengthening women’s roles in climate adaptation and mitigation. Empowering women as agents of change, through equal access to land, finance, training, innovation, and technology is vital for adoption and scaling up climate-smart agriculture (CSA). CSA must be gender-responsive, tackling social norms, technical barriers, and resource inequalities to ensure women can fully benefit from climate-smart practices. Inclusive policies, gender-sensitive extension services, and equitable financing are essential to increasing women’s adoption of CSA solutions.